In silico modeling for ex vivo placenta perfusion of nicotine - Ho, Harvey; Zhang, Shengjie; Kurosawa, Ken; Jiang, Botao; Chiba, Koji (Frontiers in Pharmacology, 2024)
Nicotine readily crosses the placenta to reach fetuses. However, membrane transporters, e.g. organic cation transporters (OCTs) play a role in the clearance of nicotine from the fetal to the maternal side, and this is rarely investigated clinically. In this work, we use an in silico model to simulate an ex vivo placenta perfusion experiment, which is the gold standard for measuring the transplacental permeability of compounds, including nicotine. The model consists of a system of seven ordinary differential equations (ODEs), where each equation represents the nicotine concentration in compartments that emulate the ex vivo experiment setup. The transport role of OCTs is simulated bi-directionally at the placenta's basal membrane (the fetal side). We show that the model can not only reproduce the actual ex vivo experiment results, but also predict the likely maternal and fetal nicotine concentrations when the OCT transporters are inhibited, which leads to a ∼12% increase in fetal nicotine concentration after two hours of OCT modulated nicotine perfusion. In conclusion, a first in silico model is proposed in this paper that can be used to simulate some subtle features of trans-placental properties of nicotine.